Hypertension and acute coronary syndromes in Romania: data from the ISACS-TC registry. (January 2014) - Dorobantu, Maria; Tautu, Oana-Florentina; Fruntelata, Ana; Calmac, Lucian; Tatu-Chitoiu, Gabriel; Bataila, Vlad; Dimulescu, Doina; Craiu, Elvira; Nanea, Tiberiu; Istvan, Albert; Babes, Katalin; Macarie, Cezar; et al.
Abstract: There is little information on the incidence and prognostic significance of arterial hypertension (HTN) in acute coronary syndromes (ACSs), especially in the east European countries. We sought to investigate a registry of ACS patients in Romania, in order to better elucidate whether hypertensive patients are at higher risk of death and deserve a tailored approach for management and follow-up. The data of this study are a framework of the International Survey of Acute Coronary Syndromes in Transitional Countries (ISACS-TC) (ClinicalTrials.gov, NCT01218776). The present analysis focused on 2286 retrospective patients admitted to 23 hospitals in Romania with a diagnosis of ACS. Among 1450 hypertensive patients, 64.5% were admitted with a diagnosis of ST elevation myocardial infarction (STEMI), while the remaining was admitted with a diagnosis of non-STEMI (NSTEMI). When compared with non-hypertensive patients, hypertensive patients were older (mean age 60.3 vs. 66.7 years, P < 0.001), were prevalently female (25.8% vs. 35.5%, P < 0.001), and had higher rates of cardiovascular risk factors as well as higher rates of prior myocardial infarction (11.2% vs. 18.3%, P < 0.001). Additionally, they had higher rates of prior stroke (4.2% vs. 11.7%, P < 0.001) and chronic heart failure (11.5% vs. 18.4%, P < 0.001). Despite this adverse clinical profile, hypertensive patients were less likely be to be admitted with Killip class ≥2 (23.1% vs. 26.6%, P < 0.001) but they were more likely to be discharged with NYHA class ≥III (10.6% vs. 7.1%, P < 0.006). There were significant higher rates of unadjusted in-hospital mortality among hypertensive older (>65 years) patients with both STEMI and NSTEMI. Hypertensive ACS patients in Romania represent a higher risk group, since they are more often discharged with NYHA class ≥ III, are older and have an adverse clinical profile. In the elderly, the outcomes of the hypertensive patients are worse than non-hypertensive patients.